Business analytics and firm performance: role of structured financial statement data. (3rd July 2018) - Whitelock, Vincent
ABSTRACT: Although business analytics has received its fair share of attention, extant research has paid insufficient attention to establishing and communicating a general understanding of the relationship between analytics and performance. In order to reduce the identified knowledge gap, this study proposes a comprehensive, theoretical framework to explain the key types of business analytics, their relationships, and how business analytics use impacts operational and financial performance. This study proposes a combination of critical systems, "holistic thinking/big picture/decision-making, " approaches to moderate key relationships to impact performance. Additionally, this study presents a case illustration of a real-world contract manufacturer, employing the proposed framework, to demonstrate the innovative use of integrated business analytics to turnaround an organization, and position it to survive, thrive, innovate, and grow. Findings indicate that firms, "overwhelmed by" and "struggling to use" data to improve business results, have a viable cost-effective framework to advance business analytics capability, in their organizations.